2008
DOI: 10.1097/ccm.0b013e3181659118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human atrial natriuretic peptide on renal function in patients undergoing abdominal aortic aneurysm repair*

Abstract: The intraoperative and postoperative infusion of low-dose hANP preserved renal function in patients undergoing abdominal aortic aneurysm repair. Further studies are needed to assess the efficacy of prophylactic hANP infusion on perioperative renal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Recent studies indicated that hANP not only regulates body fluids and blood pressure, but also exerts a renal protective effect in I/R injury [3,4,10]. In the present study, we demonstrated that I/R-induced elevation of the renal function indicators BUN and Cre were attenuated by hANP, and histologic manifestations of renal damage such as tubular epithelial loss and hemorrhage were also reduced.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Recent studies indicated that hANP not only regulates body fluids and blood pressure, but also exerts a renal protective effect in I/R injury [3,4,10]. In the present study, we demonstrated that I/R-induced elevation of the renal function indicators BUN and Cre were attenuated by hANP, and histologic manifestations of renal damage such as tubular epithelial loss and hemorrhage were also reduced.…”
Section: Discussionsupporting
confidence: 51%
“…As an important regulator of body fluids and blood pressure, hANP exerts a variety of pharmacologic effects, including natriuresis, diuresis, vasodilatation, and suppression of the reninangiotensin system [3]. A recent study reported that hANP preserved renal function in patients undergoing abdominal aortic aneurysm repair [4]; however, the renal protective mechanism of hANP is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the combination therapy of both enalapril and paricalcitol had a more marked effect and totally inhibited the rise in ANP. Several studies indicate that in addition to its effects on regulation of volume and BP, ANP can act to preserve renal function (7,34). Koga et al (25) showed in rats that ANP also has antioxidant effects as demonstrated by its ability to attenuate ROS levels in a renal ischemia-reperfusion (I/R) injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial natriuretic peptide (ANP), a hormone secreted primarily by atrial cardiomyocytes, is a potent natriuretic, diuretic and vasodilatory peptide that contributes to decreasing blood pressure [6]. Previous studies have found that human ANP (hANP) preserves renal function in patients undergoing coronary artery bypass surgery [7, 8] and abdominal aortic aneurysm repair [9]. One study showed that continuous infusion of hANP during cardiac surgery with CPB maintained postoperative renal function by preventing the activity of the RAAS [7].…”
Section: Introductionmentioning
confidence: 99%